2017
DOI: 10.1155/2017/4287890
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Ameliorates Experimental Alcoholic Liver Disease by Modulating Oxidative Stress

Abstract: The aim of this study was to investigate the hepatoprotective effects of resveratrol in alcoholic liver disease (ALD). Alcohol was administered to healthy female rats starting from 6% (v/v) and gradually increased to 20% (v/v) by the fifth week. After 16 weeks of intervention, liver enzymes (aspartate aminotransferase [AST] and alanine aminotransferase [ALT]) were analyzed using a chemistry analyzer, while hepatic antioxidant enzymes, oxidative stress markers, and caspase 3 activity were assessed using ELISA k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 38 publications
(45 reference statements)
0
11
0
Order By: Relevance
“…Resveratrol significantly reverses the decreased activities of antioxidant CAT and glutathione peroxidase (GPx). The authors also found that resveratrol also improves apoptosis and inflammation in ethanol-treated rats (He et al, 2017).…”
Section: Kasdallahmentioning
confidence: 89%
“…Resveratrol significantly reverses the decreased activities of antioxidant CAT and glutathione peroxidase (GPx). The authors also found that resveratrol also improves apoptosis and inflammation in ethanol-treated rats (He et al, 2017).…”
Section: Kasdallahmentioning
confidence: 89%
“…Additionally, these beneficial agents can alter the metabolism and production of many endogenous compounds such as ethanol, acetaldehyde, SCFAs, bile acids, and trimethylamine (TMA) by altering the compositions of the gut microbiome [ 202 , 221 ] or perhaps even ethanol and acetaldehyde, which have been shown to be produced by some gut bacterial strains [ 202 , 218 , 219 , 220 , 222 ]. These antioxidant phytochemicals and/or their gut metabolites can also suppress the increased oxidative and nitrosative/nitrative stress by inhibiting the enzymes, such as CYP2E1, NOXs, iNOS, and NF-κB [ 223 , 224 , 225 ], as listed in the Figure. Furthermore, these beneficial antioxidant compounds from dietary supplements can affect key enzymes/proteins in the cellular signaling pathways, such as AMPK [ 226 ] and hepatic Sirt-1 [ 227 ], or transcription factors, including NF-κB and PGC-1α [ 228 , 229 ], to show their biological effects, as demonstrated by polyphenols in green and black teas [ 230 ].…”
Section: The Antioxidant Properties Metabolisms and Health Benefmentioning
confidence: 99%
“…RSV is found in the skin of grapes, in berries, and peanuts, with considerably high levels in grape juice (0.19–0.96 mg/L), and red wine (1.9 ± 1.7 mg/L) [43,44,45]. RSV has been studied for its pharmacological effects, including antioxidant, anti-inflammatory, immunomodulatory, hepatoprotective, anti-cancer, anti-atherosclerotic, and anti-diabetic properties [42,46,47,48,49,50,51].…”
Section: Introductionmentioning
confidence: 99%